PEMBUATAN VIDEO KERAJINAN SILVER CLASS DALAM BAHASA JEPANG DI YAN YAN SILVER - Wayan Nurita; Ladycia Sundayra (LOKATARA SARASWATI, 2025)
Tourism in Bali remains a key economic sector for the Balinese people. According to the Bali Provincial Statistics Agency (BPS), Japanese tourists, ranked among the top 10, recorded 15,889 visitors in December 2024, a +39.19% increase from 11,415 visitors in November of the previous year. Given this reality, tourism operators in Bali are required to provide excellent service related to facilities, human resources, and products that will serve as memories when they leave Bali for their countries. One of the handicraft products produced by the Balinese community is processed silver located at Yan Silver Gianyar, which has been established since the 2000s. Many Japanese tourists visit and purchase its products as souvenirs. Silver crafts as a micro-business activity is a tool to reduce poverty by offering flexible business opportunities and numerous job opportunities and a variety of goods and services to tourists, directly and indirectly (ILO, 2012: 16). This community service activity aims to provide language training that focuses on the steps in making handicraft products at Yan Silver through videos using standard Japanese language services for Japanese tourists. This community service activity is expected to have a positive impact on improving the quality of service to Japanese tourists visiting Yan Silver so that it can become a future reference for tourism practitioners and other tourism entrepreneurs in Bali to leave a good impression in the eyes of tourists to be able to make sustainable tourism which can ultimately improve the welfare of the people in Bali.